Modeling the impacts of residential, commercial, and industrial land use on carbon footprints using kernel density function in an urban setting - Zullyadini A. Rahaman (Tanjung Malim, 2023)
Modeling the impacts of residential, commercial, and industrial land use on carbon footprints using kernel density function in an urban setting by Zullyadini A. Rahaman